PENINGKATAN RESOLUSI SENSOR LOAD CELL PADA TIMBANGAN ELEKTRONIK - Eka Mandayatma (Politeknik Negeri Malang, 2018)
Electronic scales are heavy gauges that are widely used both in the laboratory and in the business world. One of the main sensors of electronic scales is the load cell. The direct use of load cell will result in the achievement of the standard resolution of the load cell or ADC system used, so the resolution of the scales will be quite low as it is determined only by the load cell measurement range and the ADC resolution where the dynamic range of the ADC is not reached.In this article will be made electronic efforts to increase the resolution of the scales so that the accuracy of weighing can be better. Improved resolution attempts are made with electronic signal processor and conditioners, among others, by amplifying, summing and leveling amplifiers and to prevent noise being attempted by filtering. Data processing is done by comparing the resolution value of Load cell without signal conditioner and load cell resolution with signal conditioner. Load Cell with a load range of 0 - 5 kg in conditioning with 200x gain obtained output 113 mV to 1200 mV. With a standard ADC at a resolution of 20 mV / bit will be obtained 0000 0110 to 0011 1110 By adding a Leveling Amplifier circuit obtained output 48 mV for load 0 kg and 4.87 Volt for 5 kg load, ADC output in the range 0000 0010 to 1111 1100. Usage ADC without leveling 21% and with 98% leveling. Without leveling weighing resolution is 89 grm / bit and with 20 grm / bit leveling. Increased weighing resolution of 345%.